EGYPTIAN WAX DEPILATION: ORIGIN, TECHNIQUE AND EFFECTS ON SKIN HEALTH (International Seven Journal of Multidisciplinary, 2023)
The Egyptian wax hair removal method, with ancient origins, has gained prominence in contemporary aesthetics for combining tradition, effectiveness, and sustainability. This study aimed to investigate the origin, technique, and dermatological effects of Egyptian wax, emphasizing its therapeutic benefits and professional applicability. The research was based on a qualitative and descriptive literature review, gathering academic and technical publications addressing the natural composition of the wax, required care, and physiological reactions observed after the procedure. The analysis revealed that Egyptian wax, composed of honey, sugar, and lemon, provides efficient hair removal without harming the skin, offering moisturizing, antiseptic, and healing properties. The method favors epidermal regeneration, reduces folliculitis incidence, and improves skin texture and radiance. In addition to delivering aesthetic results, the technique contributes to well-being and environmental awareness, as it employs biodegradable ingredients and minimizes chemical impacts. Therefore, Egyptian wax is consolidated as a safe, therapeutic, and environmentally responsible practice, reaffirming the relevance of traditional knowledge integrated with modern cosmetology.